Green Images in Indian Rock Art - Meenakshi Dubey Pathak (Arts)
In India, particularly in central India, a large number of early images were created using green pigments. Within the green images or images in the earliest style, one can see that some extremely naturalistic animal figures were made with green and dark red, and rarely in a polychrome (green, red and yellow) style. Only a few images have survived. The human figures, represented in a typical S shape in a smaller size or with an S-twist body in single outline, are highly artistic and very dynamic figures. The figures are mostly represented as dancers. Wakankar found green pigment in the Upper Paleolithic levels in Bhimbetka, and hence these images were put in the Upper Paleolithic period. These green images mainly exist in rock art sites in the surroundings of Bhimbetka in the Raisen, Sehore and Vidisha districts.